Use of Kinleith Forest by native New Zealand bats and effects of forestry : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Ecology at Massey University - Moore, Geraldine Elaine (Massey University, 2001)
New Zealand's vulnerable microbats, the long-tailed bat (Chalinolobus tuberculatus, Vespertilionidae) and short-tailed bat (Mystacina tuberculata, Mystacinidae), are typically tree-roosting and generally associated with indigenous forest. However, bats have been seen at the edge of Carter Holt Harvey Forests' central North Island Kinleith Forest, a 131,000 ha exotic forest predominantly in Pinus radiata. Requested by Carter Holt Harvey Forests, this study investigates bat presence and distribution in Kinleith Forest, forest use by long-tailed bats, and the effects of forestry practices on bats, with focus on tree felling operations. It is the first comprehensive study of native bats' use of exotic plantation forest in New Zealand. A broad-scale bat detector-based survey of 32 disparate sites, and comprising 720.5 km of driving transects over three routes, found long-tailed bats to be widespread in Kinleith Forest. In places activity was high, on some nights exceeding 60 bat passes/hour, or 100 passes/night, and at one site, averaging 46.0 passes/night (n = 189 bat detector-nights from throughout the year). Given the decline in this species elsewhere, it is significant that long-tailed bats are present in some areas from which they were known historically. Mapping of bat sites in relation to forest type indicates long-tailed bats may have a fairly continuous distribution in the central North Island. Results suggest that instead of approaching unsurveyed plantation forests with the expectation that long-tailed bats are absent, they should be assumed present until proven otherwise. Anecdotal evidence of short-tailed bats, and of Dactylanthus taylorii – a rare plant they naturally pollinate, indicates short-tailed bats could potentially be present in Kinleith Forest. Bat activity monitoring in adjacent forest interior and road habitats showed long-tailed bats commonly used roads in young (without canopy closure) and mature P. radiata forest, and podocarp broadleaf forest. Bats probably favoured roads for reasons of habitat structure, though roads may also play a role in navigation. This behaviour can be used to advantage when surveying for long-tailed bats in plantation forest. Survey work identified long-tailed bats to be present in all topographies and a range of habitats including harvested/unstocked land, young P. radiata forest, and mature (≥ 17 years) P. radiata, Eucalyptus spp., Pseudotsuga menziesii and Sequoia sempervirens forest, wetlands, and native forest remnants. Comparison of 46 "bat habitats" with habitat availability along 194 km of transects revealed long-tailed bats to select older pine forest and generally avoid unstocked land or younger forest. This pattern is supported by findings from monitoring work in young and mature pine forest. Older pine forest retains more heat, has a different understorey, and may offer more shelter than younger forest, potentially influencing insect prey abundance and bat activity. Bats' differential use of habitat may partially explain the lower number of bat encounters in the Wainui area than the Galaxy area. Six sites, including a wetland, older pine forest, and areas in or adjacent to native forest, had high bat activity. The relative importance of exotic plantation forest and native podocarp broadleaf forest reserve land to foraging long-tailed bats was investigated in a replicated bat detector-based study. Insect abundance and ambient temperature were also monitored. Bat activity and foraging activity were much greater in the plantation forest than the native forest, possibly because of the greater abundance of moths – important prey. Forest type was the best predictor of bat activity. Anecdotal accounts indicated several bat roosts to be in production trees (P. radiata), including old crop trees. One record was of a roost in a barely noticeable crevice in a 30-year-old pine, others were from areas of native forest, rocky crevices and a cave. Four accounts were of communal roosts. There is evidence that maternity roosts may occur in production forest. Most observations were made during the process of habitat modification and so roosts no longer exist. At least one possible communal roost was identified from bat activity data. A review of roosting ecology suggests that while highly mobile, long-tailed bats use many roosts in a small area, often roost near forest edges, are highly selective of roosts, and may face inter- and intra-specific competition for roosts. Long-tailed bats may be very sensitive to roost site disturbance and habitat fragmentation. Tree felling, an important part of forestry, could threaten long-tailed bats at an individual and a population level by causing injury or death, reducing available habitat, and isolating bat groups. However, tree felling could create foraging (e.g. edge) habitat and facilitate access for bats. Overall, effects are likely to depend on the scale of operations. Other forestry operations which could negatively affect long-tailed bats include site preparation, pesticide use, infrastructure works, transportation and quarrying. Pest mammal control operations and the conservation of cave, wetland and reserve areas potentially benefit long-tailed bats in Kinleith Forest. The complex habitat mosaic may be favourable to long-tailed bats. However, there are many questions yet to be answered. Sensitive management may be needed to ensure bat survival in Kinleith Forest. Long-tailed bats probably prey on a number of forestry pests including Helicoverpa armigera and may be an effective biocontrol agent. Artificial roost boxes could be used to encourage bats in this role and reduce the number of bats potentially harmed in tree felling operations.
Keywords: New Zealand -- Kinleith Forest region; Chalinolobus tuberculatus; Carollia perspicillata; Bats -- Ecology; Forests and forestry